Comprehensive analysis of DOK family genes expression, immune characteristics, and drug sensitivity in human tumors - Yongjun Guan; Man Li; Zhendong Qiu; Junhui Xu; Yichao Zhang; Ning Hu; Xuanzhe Zhang; Wenyi Guo; Jingping Yuan; Qiao Shi; Weixing Wang (Journal of Advanced Research, 2022)
Introduction: DOK is a new type of regulatory protein family that participates in the regulation of tumor cell growth. However, most of the studies are conducted in cell lines, and systematic studies have not been conducted in human tumors. Objectives: We conducted a comprehensive analysis of DOK based on its expression profile and its relationship with patient survival, immune infiltration, tumor microenvironment, and drug sensitivity. Methods: We used the TCGA database to analyze the correlation between DOK family gene expression and prognosis and clinical stage. The protein expression of DOK in tumor tissues was analyzed by immunohistochemistry. Use the cBioPortal database to analyze the alteration frequency in DOK family genes in human tumors. In addition, we used ESTIMATE algorithm and TIMER website to analyze the correlation between DOK family genes and tumor immunity. Finally, we further analyzed the relationship between DOK family genes and tumor stemness and the sensitivity of cancer cells to chemotherapy. Results: We conducted a comprehensive analysis of DOK family genes based on its expression profile and its relationship with patient survival. We also confirmed this conclusion by immunohistochemistry. The expression of DOK family genes is related to OS, clinical stage, tumor mutation, methylation, CNV, and SNV. DOK family genes are significantly associated with poor prognosis of UVM. DOK1-DOK3 has obvious correlation with tumor immunity. DOK2 can increase the sensitivity of chemotherapy drugs, while DOK4 reduces the sensitivity of multiple chemotherapy drugs. In addition, the expression level of DOK family genes is significantly correlated with the activity of cancer marker-related pathways. Conclusions: DOK plays a role of tumor suppressor gene or tumor-promoting gene in different tumors. However, DOK family genes play a role in promoting cancer in UVM. DOK family genes are significantly associated with drug sensitivity.